2016
DOI: 10.1111/jace.14158
|View full text |Cite
|
Sign up to set email alerts
|

Flash Spark Plasma Sintering (FSPS) of α and β SiC

Abstract: A novel processing methodology that allows combined preheating and Flash-SPS (FSPS) of silicon carbide-based materials has been developed. Beta-SiC (+10 wt% B 4 C) powders were densified (Ф 20 mm) up to 96% of their theoretical density in 17 s under an applied pressure of 16 MPa (5 kN). The flash event was attributed to the sharp positive temperature dependence of the electrical conductivity (thermal runaway) of SiC, and a sudden increase in electric power absorption (Joule heating) of the samples after a suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 40 publications
3
109
0
1
Order By: Relevance
“…As shown in Figure 5, the transition from voltage to current control mode creates a power spike [13] which is not to be confused with NTC behaviour of the material. It has been clearly demonstrated that the sample temperature follows the powder dissipation [61]. Even if this control mode ( Figure 5(a)) results in a near instantaneous (5 s) consolidation of the materials [5], it might not be ideal to study or understand the mechanism involved in this process due to its extremely high rate.…”
Section: Experimental Configurations For Fsmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Figure 5, the transition from voltage to current control mode creates a power spike [13] which is not to be confused with NTC behaviour of the material. It has been clearly demonstrated that the sample temperature follows the powder dissipation [61]. Even if this control mode ( Figure 5(a)) results in a near instantaneous (5 s) consolidation of the materials [5], it might not be ideal to study or understand the mechanism involved in this process due to its extremely high rate.…”
Section: Experimental Configurations For Fsmentioning
confidence: 99%
“…In the case FS of semiconductors, such as SiC [61] and B 4 C [32], there is a metal-semiconductor junction, which produces Schottky barriers.…”
Section: Effects Of Electrode Materials and Its Catalytic Activitymentioning
confidence: 99%
See 3 more Smart Citations